Peran Audit Siklus Utang dalam Memastikan Kepatuhan dan Efektivitas Pengelolaan Liabilitas Entitas Bisnis Modern - Fahmi Andika; Sahrul Ramadhan; Masyhuri Masyhuri (Journal of Economic and Business Advancement, 2025)
This study aims to analyze the role of debt cycle audits in ensuring compliance and effectiveness in managing the liabilities of modern business entities, given that liabilities through corporate debt pose a high risk to liquidity and misstatement, thus requiring systematic and professional audit oversight. The research uses a literature review as a qualitative approach by examining various academic literature, professional standards, and relevant empirical research results on debt cycle audit practices, auditor challenges, and the concepts of internal control and reporting transparency. The results show that effective debt cycle auditing involves document verification, disclosure of Key Audit Matters (KAM), and auditor competence and independence, which play a significant role in improving the quality of audit opinions, reducing debt costs, and strengthening corporate financial stability. The discussion emphasizes that the effectiveness of debt cycle auditing depends on a combination of strict internal controls, supporting information technology, and auditor integrity in carrying out audit procedures.